The design of an extended length helium pulsating heat pipe experiment. Issue 1 (1st May 2022) - Kossel, L; Pfotenhauer, J; Miller, F
Abstract: Pulsating heat pipes, also known as PHPs, are passive two-phase heat transfer devices capable of moving heat at cryogenic temperatures with high effective thermal conductivities around two orders of magnitude higher than copper. A recent Helium Pulsating Heat Pipe experiment demonstrated a surprising phenomenon, where Helium PHPs of different lengths (300 mm and 1000 mm) displayed the same thermal conductance at equal heat loads. The purpose of this research is to experimentally characterize this apparent length-independence and determine the size limits for Helium PHPs. An experimental approach is developed where three additional Helium PHP experiments will be conducted with the same operating parameters as the original experiment except with extended adiabatic lengths – 1.25 m, 1.5 m, and 1.75 m. All PHPs considered in this study are in the vertical orientation and are bottom-heated. This will give five complete sets of data from which the influence of length on helium pulsating heat pipes' performance may be analysed. This paper serves as a work-in-progress report describing the experimental design and fabrication of these Helium PHP experiments.